56.4k views
4 votes
Which expressions are equivalent to 2r+(t+r)

Choose all answers that apply:
A: 2rt+4r
B: r+t
C: None of the above

User Dan Klos
by
6.2k points

2 Answers

3 votes

Answer:

C. None of the above

Explanation:

User Vikramls
by
6.3k points
4 votes

Answer:

Option C -> None of the above.

Explanation:

Given-

2 r + ( t + r )

⇒ 2 r + t + r

⇒ 2 r + r + t

⇒ 3 r + t

∵ 2 r + ( t + r ) = 3 r + t.

∴ The given expression is equivalent to Option C : None of the above.

User CoryG
by
6.0k points